2015
DOI: 10.1039/c5py01557j
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of hydrogen peroxide-responsive polymeric micelles of biodegradable triblock polycarbonates as a potential drug delivery platform with ratiometric fluorescence signaling

Abstract: Two micelles of amphiphilic triblock polycarbonates with different H2O2-reactive core-forming blocks manifest disparate H2O2-induced disaggregation behaviors of micelles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 87 publications
2
9
0
Order By: Relevance
“…the non-proton transfer, normal emission). Such phototautomerism offers ample fundamental insights and can be specified with a barrierless process, a barrier induced, or a reversible process. On the other hand, the diversification in the ESIPT mechanism renders different emission properties in terms of single, dual, and even multiple emissions that can be fine-tuned by varying the functionality, offering the versatility in applications such as in sensing, bioimaging, organic lasing, and light-emitting diodes. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…the non-proton transfer, normal emission). Such phototautomerism offers ample fundamental insights and can be specified with a barrierless process, a barrier induced, or a reversible process. On the other hand, the diversification in the ESIPT mechanism renders different emission properties in terms of single, dual, and even multiple emissions that can be fine-tuned by varying the functionality, offering the versatility in applications such as in sensing, bioimaging, organic lasing, and light-emitting diodes. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…Fu et al reported dual‐function theranostic micelles of amphiphilic triblock PCs that allow the possible targeted drug release and simultaneous ratiometric fluorescence sensing in response to H 2 O 2 . In this case, the disassembly and fluorescence behaviors of micelles are highly influenced by the structural features of the H 2 O 2 ‐reactive core‐forming HPO blocks . Moreover, Phan et al developed a new pH‐/temperature‐sensitive, biocompatible, biodegradable, and injectable hydrogel based on PEG‐ b ‐PACU copolymers for the sustained delivery of human growth hormone.…”
Section: Applicationsmentioning
confidence: 99%
“…By introducing host-guest interactions in C3Ms, the stability against salt and competing cyclodextrin could be adjusted by finely tuning the charge of the adamantane guest (15). Here, we selected ferrocene as guest for its well-known 1:1 inclusion complex with β-CD, with an association constant (k a ) around 4.1 10 3 M −1 (in its reduced form) (21)(22)(23)(24)(25)(26) and for its responsivity towards mild oxidants, such as FeCl 3 , AgNO 3 , I 2 (27)(28)(29) or H 2 O 2 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). The oxidation reaction of ferrocene to ferrocenium (Fc + ) causes consequently the dissociation of the Fc + from the β-CD (k a 15 M −1 ).…”
Section: Introductionmentioning
confidence: 99%